Existential nihilism in Ignatius Mabasa’s Poetry: implications for the development of the human factor - Tembo, Charles; Mutasa, Dave; Maganga, Allan T. (2022)
This article finds its fountainhead in the trend in Ignatius Mabasa’s poetry to cast existential nihilism as a way of life. That is, despite the fact that the poetry grapples with big issues that breed social malaise, it lacks the necessary optimism that is indispensable to struggles to transcend life’s challenges. Hopelessness and despair have no place in Africa and literature has to recognise this fact. African people celebrate agency and revolution. Be that as it may, the poems explicated in this paper seem to be inspired by the Euro-modernist tradition which canonises meaninglessness or the absurdity of life. The centrepiece of this paper is that Mabasa abstracts his art and subsequently his audience from African existential philosophy, a philosophy premised on resistance and optimistic struggle. It is largely lachrymal art that negates struggle and transcendence. Contrary to optimism in the face of the inevitability of struggle …